Comprehensive Impact Assessment of Watershed Interventions in South Pennaiyar Catchment of Tamil Nadu, India - S. Manivannan; O. P. S. Khola; V. Kasthuri Thilagam (Recent Progress in Science and Technology Vol. 5, 2023)
The effects of comprehensive interventions in erosion control, increasing water accessibility, developing agroforestry, managing natural resources sustainably, increasing agricultural productivity, and addressing the socioeconomic needs of farmers were investigated. The impacts of major watershed development programmes have been outlined in terms of biophysical impacts, environmental impacts, socio-economic impacts and overall economic impacts. It is pointed out that the watershed development activities have made significant positive impacts on various biophysical aspects such as soil and water conservation, soil fertility, soil and water erosion in cropped area, changes in cropping pattern, cropping intensity, production and productivity of crops. The study was conducted in South Pennaiyar catchment in Dharmapuri, Salem, Villupuram, Vellore, Thiruvannamalai districts of Tamil Nadu for three years during 2012-14. By employing stratified random sampling method 15 study watersheds (SWS) were selected and the benchmark data collected by the PIA at the time of project planning were used for the study and analyzed through budgeting techniques or appropriate statistics. The evaluation study reveals that 8 to 10 percent reduction of runoff. Soil loss also reduced in the range of 1.1 to 1.9 t ha-1yr-1. Gully control structures made their impacts in terms of arresting silts at the rate of about 10.1 cum yr-1 in one watershed and stabilized the gullies. Increased water table in the range of 0.32 and 0.93 m with increased duration of water availability in wells for more than 9 months and increased recuperation rate (1.8 to 6.5 per cent) were observed. An additional surface storage capacity of 26.4 ha - m per watershed was created due to watershed interventions. The Net Present value of the project is about Rs. 52,238 lakhs without considering intangible benefits. The economic soundness of the project is also amply indicated by BCR (1.65:1) and IRR (53%) and the whole investment made in the project can be recovered within seven years. The NPV of the project further improved by inclusion of monetary value of the nutrient due to reduced soil erosion. The value of NPV was more than Rs. 63,968 Lakhs with 1.72 BCR and 65.5 % IRR. It is advised that the river valley project in Tamil Nadu’s South Pennaiyar catchment be given priority in order to promote sustainable agricultural growth in the river and reservoir catchments.The evaluation study conclude that such projects should be taken in the catchments of reservoirs on priority in a more concentrated and coordinated manner with active participation of local community, guided by technological requirement rather than the rigid government norms along with technical back stopping mechanism and withdrawal strategy.